2017
DOI: 10.7717/peerj.4086
|View full text |Cite
|
Sign up to set email alerts
|

Do rotational shear-cushioning shoes influence horizontal ground reaction forces and perceived comfort during basketball cutting maneuvers?

Abstract: BackgroundCourt shoe designs predominantly focus on reducing excessive vertical ground reaction force, but shear force cushioning has received little attention in the basketball population. We aimed to examine the effect of a novel shoe-cushioning design on both resultant horizontal ground reaction forces and comfort perception during two basketball-specific cutting movements.MethodsFifteen university team basketball players performed lateral shuffling and 45-degree sidestep cutting at maximum effort in basket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…While it could not be identified precisely how this small difference could influence the study outcomes, the only possibility that exist is the shoe with higher heel-to-toe drop could possibly offer a slight extra cushioning feature to the shoe. However, the study by Lam et al ( 2017 ) identified that cushioning provides no advantage to the horizontal ground reaction force component that is crucial during short-exertion, high-intensity movement such as short-distance sprint and change of direction tasks. Therefore, it can be suggested that the influence of heel-to-toe drop difference was minimal in this study.…”
Section: Discussionmentioning
confidence: 99%
“…While it could not be identified precisely how this small difference could influence the study outcomes, the only possibility that exist is the shoe with higher heel-to-toe drop could possibly offer a slight extra cushioning feature to the shoe. However, the study by Lam et al ( 2017 ) identified that cushioning provides no advantage to the horizontal ground reaction force component that is crucial during short-exertion, high-intensity movement such as short-distance sprint and change of direction tasks. Therefore, it can be suggested that the influence of heel-to-toe drop difference was minimal in this study.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, others have shown that overall comfort level could be perceived in a 45°side-cutting task when examining the effects of a shear cushioning system in the forefoot. 5 Nin et al 17 found that cushioning intensity of basketball shoes can be consistently rated according to midsole hardness conditions in layup, shot-blocking, and drop-landing tasks, but rearfoot stability could only be differentiated during the layup task. This suggests that human perception to athletic footwear properties may be task specific and function specific, while a specific degree of functional shoe modification is needed to reach athlete awareness.…”
Section: Subjective Perceptionmentioning
confidence: 99%
“…Regarding injury prevention, it is desirable if footwear midsole material can minimize the risk of sportsrelated injuries. 5 During basketball games, non-contact lower extremity injuries, such as anterior cruciate ligament (ACL) injuries and ankle ligament sprains, are common. 6 Players often perform cutting maneuvers to change direction, which impose high pressure in the forefoot region 7 and great loading in the lower extremities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact force and pressure distribution characteristics between the feet and the shoes must be understood to effectively optimize the technical movements, reduce foot injuries, and improve the design of specialized shoes [6]. However, the existing studies on foot loading have mainly focused on common gait characteristics, such as walking and running [7,8], and studies on specific sports maneuvers, such as cross-over running and lay-up jumping [9][10][11], are limited.…”
Section: Introductionmentioning
confidence: 99%